A History of the Psychology Schools at Adelaide's Universities - Winefield, Tony; Nettelbeck, Ted (University of Adelaide Press, 2016)
This book commemorates the history of the psychology schools in Adelaide's three Universities: The University of Adelaide, Flinders University and the University of South Australia. Its publication in 2016 coincides with their 60th, 50th and 25th birthdays respectively. Their core activities comprise undergraduate teaching, postgraduate research training, research and postgraduate professional training.